(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2015)
1,3-Thiazolylidenehydrazinylidene ethylpyridinium bromide monohydrate, 1,3-thiazolylidenehydrazinium bromide and 1,3-thiazolylidenehydrazine derivatives were synthesized by heterocyclization of 2-(1-substituted ethylidene) hydrazinecarbothioamides, characterized and screened for their anti-bacterial activities. The structures of synthesized compounds were established by spectroscopic (IR, 1H, 13C-NMR, Mass) and X-ray analyses.